2020
DOI: 10.1007/s11249-020-01293-x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Behaviour of Synovene and Oleamide in Oil Adsorbed on Steel

Abstract: Oleamide and Synovene lubricant additives when mixed together show a clear co-operative effect leading to friction and wear reduction. Sum Frequency Generation vibrational spectroscopy has been used to record in situ spectra of these additives with the aim of understanding the behaviour of these molecules when adsorbed on steel immersed in a model base oil at pre-selected temperatures. The spectra of the individual components and of mixtures have been recorded up to 130 °C. Individual spectra from both molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Therefore, the increase in friction at 140°C cannot be due to loss of molecules from the surface. Recently, sum frequency generation spectroscopy studies have shown oleamide to exhibit maximum ordered adsorption at ~70°C 44 which may be the reason for improvement in frictional performance at the intermediate temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the increase in friction at 140°C cannot be due to loss of molecules from the surface. Recently, sum frequency generation spectroscopy studies have shown oleamide to exhibit maximum ordered adsorption at ~70°C 44 which may be the reason for improvement in frictional performance at the intermediate temperature.…”
Section: Resultsmentioning
confidence: 99%
“…An in-depth study was conducted on this basis, as shown in Fig. 7(c) [83]. Co-operative behavior was observed between different friction modifier molecules.…”
Section: Friction Interface Behaviors In Complex Oil-based Lubricatinmentioning
confidence: 99%
“…In general, the friction modifications used in engine oil are metal friction modifications (such as didithiophosphate zinc (ZDDP), organic molybdenum [9,10], etc.) and non-metallic friction modifications (such as oleamide [11], glycerol monooleate [3,12,13], etc.). Metal friction improvement agents are mostly metal or metal compounds containing sulfur and phosphorus.…”
Section: Introductionmentioning
confidence: 99%